Utilização de compósito de fibra de vidro/resina epóxi para reforço estrutural de vigas de concreto armado - Andrade, Nathan Pereira de [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Factors such as project and execution errors, lack of maintenance and inspection, and changes in loading cause deficiencies to reinforced concrete structures. In this sense there is the need of application of structural reinforcement systems. This study presents some of the techniques of structural reinforcement, emphasizing the manufacturing process, implementation and execution of structural reinforcement with composite material based on pre-impregnated of glass fiber fabric type plain weave 1 x 1 and epoxy resin. Beams made of steel reinforced concrete, composite material beams and hybrid (steel reinforced beams and composite beams combined together) were submitted to 4 points flexural test. Experimental and calculated results for the dimensioning of the beams were compared, allowing the validation of the calculation method and its implementation. It was possible to notice both the efficiency of the composite material applied to the reinforcement of steel/concrete beams, as well as the efficiency of the calculation models applied in this work

Fatores como erros de projeto e execução, falta de manutenção e vistorias, além de mudanças no carregamento trazem deficiências às estruturas de concreto armado. Nesse sentido há a necessidade da utilização de sistemas de reforços estruturais. Esse trabalho apresenta algumas das técnicas de reforço estrutural, com ênfase no processo de fabricação, aplicação e execução de reforço estrutural com compósito fabricado a partir de pré-impregnado de tecido de fibra de vidro tipo plain weave 1x1 e resina epóxi. Foram realizados ensaios de flexão de 4 pontos em vigas de concreto armado, placas de compósito e em vigas híbridas (vigas de concreto armado reforçadas com compósito). Com os resultados foram feitas comparações entre os valores experimentais e os valores calculados pelos métodos de dimensionamento, possibilitando a aferição da metodologia de cálculo e sua aplicação em vigas com reforço estrutural. Foi possível perceber tanto a eficiência do sistema polimérico reforçado com fibras aplicado para o reforço de vigas de concreto armado, como também a eficiência dos modelos de cálculo utilizados
Use of fiberglass composite / epoxy resin for structural reinforcement of reinforced concrete beams
Keywords: Compósitos poliméricos; Resinas epoxi; Concreto armado; Fibras de vidro; Polymeric composites